ANOMALOUS GEOELECTRICAL AND GEOMAGNETIC SIGNALS OBSERVED AT SOUTHERN BOSO PENINSULA, JAPAN - Takahashi I.; Hattori K.; Yoshino C.; Isezaki N.; Harada M. (My University, 2007)
Geoelectrical and geomagnetic fluctuations are considered the end product of several geophysical phenomena. In particular these signals measured in seismically active areas can be attributed to stress and strain changes associated with earthquakes. The complexity of this problem has suggested the development of advanced sophysticated methods to investigate the heterogeneous nature of these fluctuations. In this paper, we analyzed the time dynamics of short-term variability of geoelectrical potential differences and geomagnetic fields obsereved at Kiyosumi (KYS), Uchiura (UCU), and Fudago (FDG) stations, located in the southern part of Boso Peninsula, one of the most seismically active areas in Japan. Anomalous changes in electric and magnetic fields are obeserved in mid-night on October 6, 2002. the anomalous signals observed on October 6, 2002 are different from those originated from the train and other cultural noises according to the investigation on preferred directions of geoelectric field. The investigation of simultaneous geomagnetic field changes suggest that the source of the electromagnetic change might be generated by underground current because of the polarity pattern oberved at KYS, UCU and FDG. Therefore, electrokinetic assumption under the ground seems one of the possible solutions for the generation of anomalous signals. It is important to understand the ULF electromagnetic environment for the study on the preparation process of crustal activity and systematic understanding both electromagnetic and seismic phenomena.
Keywords: DIRECTION OF SIGNAL ARRIVAL; GEOELECTRICAL POTENTIAL DIFFERENCES; ULF ELECTROMAGNETIC ENVIRONMENT; UNDERSTANDING THE PREPARATION PROCESS OF CRUSTAL ACTIVITY